A precise metallicity and carbon-to-oxygen ratio for a warm giant exoplanet from its panchromatic JWST emission spectrum - Lindsey S. Wiser; Taylor J. Bell; Michael R. Line; Everett Schlawin; Thomas G. Beatty; Luis Welbanks; Thomas P. Greene; Vivien Parmentier; Matthew M. Murphy; Jonathan J. Fortney; Kenny Arnold; Nishil Mehta; et al. (Proceedings of the National Academy of Sciences, 2025)
WASP-80 b, a warm sub-Jovian (equilibrium temperature ∼ 820 K, 0.5 Jupiter masses), presents an opportunity to characterize a rare gas giant exoplanet around a low-mass star. In addition, its moderate temperature enables its atmosphere to host a range of carbon and oxygen species (H 2 O, CH 4 , CO, CO 2 , NH 3 ). In this paper, we present a panchromatic emission spectrum of WASP-80 b, the first gas giant around a late K/early M-dwarf star and the coolest planet for which the James Webb Space Telescope has obtained a complete emission spectrum spanning 2.4 to 12 μ m, including NIRCam F322W2 (2.4 to 4 μ m) and F444W (4 to 5 μ m), and MIRI LRS (5 to 12 μ m). We report confident detections of H 2 O, CH 4 , CO, and CO 2 , and a tentative detection of NH 3 . We estimate WASP-80 b’s atmospheric metallicity and carbon-to-oxygen ratio and compare them with estimates for other gas giants. Despite the relative rarity of giant planets around low-mass stars, we find that WASP-80 b’s composition is consistent with other hot gas giants, suggesting that the formation pathway of WASP-80 b may not be dissimilar from hot gas giants around higher-mass stars.